Lower Body Weight in Men, an Epidemiological Predictor of Enlarged Left Atrium in Sinus Rhythm Patients with Dilated Heart - Bakalli, A; Georgievska-Ismail L; Musliu, N; Kocinaj, D (Wolters Kluwer - Medknow, 2016)
Background/Aims: The source of thrombi in patients with dilated cardiomyopathy is not necessarily from the dilated left ventricle. Left atrium (LA) and left atrial appendage (LAA) might be in charge for relatively high rate of systemic embolizations in these patients. The main aim of our study was to identify epidemiological predictors in sinus rhythm patients with dilated heart for LA and LAA dilation and/or dysfunction. Patients and Methods: This was a prospective cross-sectional study conducted from 2009 to 2014 in 101 sinus rhythm patients with dilated heart. We excluded patients with swallowing problems, acute myocardial infarction, atrial fibrillation/flutter, severe systolic dysfunction, mechanical valves, oral anticoagulation therapy, and/or patients with a history of stroke/systemic thromboembolic event. Results: Mean patient age was 58.13 ± 12.66 years and 69.3% were men. Hypertension was encountered in 51% of our patients, 56% of them had a history of coronary artery disease, 30% had diabetes, 25% had dyslipidemia, 30% were smokers, whereas 10% were alcoholics. Mean LA dimensions resulted higher than reference values, whereas 86% of our patients had LAA dysfunction. Male gender was an independent predictor for LA diameter dilation (95% confidence interval [CI]: 1.765–9.078, P = 0.005), while lower body weight was a predictor for enlargement of LA area (95% CI: 0.044–0.351, P = 0.014) and LA volume (95% CI: 0.160–2.067, P = 0.024). Conclusion: Male patients with dilated cardiomyopathy at sinus rhythm with lower body weight tend to have larger LA and consequently might be at higher risk of developing atrial thrombus and its subsequent consequences.
Keywords: body weight; dilated cardiomyopathy; left atrial appendage; left atrium; stroke prevention